Validity of a Digital Poster-Based Laboratory Guide on the Effect of Coconut Water on Aloe vera Growth to Foster Students’ Critical Thinking Skills - Sandi Laili Magfiroh; Imas Cintamulya (Integrated Science Education Journal, 2026)
Purpose of the study: The purpose of this study is to design a valid digital poster-based learning medium on the effects of coconut water on the growth of Aloe vera plants and to describe the validity of the designed digital poster-based learning. Methodology: This study employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate), but was limited to the Develop stage. The study focused solely on the validity testing phase and did not include testing for practicality or effectiveness. The validation process involved three expert validators, comprising one biology lecturer and two biology teachers, selected through purposive sampling. Data were collected using a validation sheet that assessed content, presentation, language, and graphics. The collected data were analyzed descriptively using percentage-based validity criteria. Main Findings: The digital poster-based laboratory guide on the effect of coconut water on the growth of Aloe vera was categorized as a highly valid resource, with an average validity score of 92.7%. The content aspect scored 93.3%, the organization 90.8%, the language 92.3%, and the graphics 94.4%. These findings indicate that the developed material is suitable for use as a biology learning resource. Novelty/Originality of this study: The novelty of this study lies in the development of digital poster-based practical guidance learning materials that integrate local resources, specifically coconut water and Aloe vera plants, thereby not only presenting information visually but also guiding students towards hands-on activities designed to develop critical thinking skills.